PENETAPAN KADAR TANIN DAN UJI KEMAMPUAN EKSTRAK DAUN GAMAL (Gliricidia sepium) SEBAGAI INHIBITOR KOROSI LOGAM TEMBAGA (Cu) - Lapailaka, Titus; Edamuli, Tri O. N.; Kadang, Luther (Chemistry Notes, 2023)
A study has been carried out to determine the levels of tannins and the effectiveness of Gamal leaf extract (Gliricidia sepium) as a corrosion inhibitor for copper (Cu). The objectives of this research were to determine the tannin content in gamal leaf extract, observe the corrosion rate of copper with varying concentrations of the extract, identify the optimal soaking time, and evaluate the inhibitory properties of gamal leaf extract on copper corrosion. Gamal leaf extract was obtained through maceration and confirmed to contain tannins using phytochemical tests. The corrosion rate and inhibition efficiency were measured using the weight loss method. The results indicated that the gamal leaf extract contained 40.42% tannins. A concentration of 10% of gamal leaf extract reduced the corrosion rate of copper in a NaCl solution, demonstrating the highest inhibition efficiency at 80.16%. It was observed that increasing the concentration of the inhibitor and prolonging the immersion time led to lower corrosion rates. In the case of a NaCl solution as the corrosion medium, the highest concentration of gamal leaf extract used was 10%, and the longest immersion time was 9 days, resulting in a corrosion rate of 0.0593 cm/year.